Second Five Year Plan of Delhi Union Territory - Planning Commission (Planning Commission)
Following the re-organisation of States and the abolition of Part “C” States, Delhi became a Union Territory with effect from 1st November, 1956. Before 1912, Delhi city was the headquarters of a Division which had been constituted after the annexation of Delhi by the British. The Division comprised the districts of Simla, Hissar, Rohtak, Delhi, Ambala, Karnal and Gurgaon. In 1912, however, a separate Delhi Province was constituted by dissolving the Delhi District and transferring Sonepat Tehsil to Rohtak District and parts of Ballabgarh Tehsil to the Gurgaon District.
The Directorate of Public Relations Delhi Administration